Photodynamic therapy induced cell cycle arrest and cancer cell synchronization: review - Moloudi, Kave; Abrahamse, Heidi; George, Blassan P. (Frontiers in Oncology, 2023)
Cell cycle arrest (CCA) is seen as a prime candidate for effective cancer therapy. This mechanism can helps researchers to create new treatments to target cancer cells at particular stages of the cell cycle (CC). The CCA is characteristic of various therapeutic modalities, including radiation (RT) and chemotherapy (CT), which synchronizes the cells and facilitates the standardization of radiochemotherapy protocols. Although, it was discovered that photodynamic treatment (PDT) had a biological effect on CCA in cancer cells but the mechanism remains unclear. Furthermore, besides conventional forms of cell death such as apoptosis, autophagy, and necrosis, various unconventional types of cell death including pyroptosis, mitotic catastrophe, paraptosis, ferroptosis, necroptosis, and parthanatos after PDT have been reported. Thus, a variety of elements, such as oxygen, the tumor's microenvironment, the characteristics of light, and photosensitizer (PS), influence the effectiveness of the PDT treatment, which have not yet been studied clearly. This review focuses on CCA induced by PDT for a variety of PSs agents on various cell lines. The CCA by PDT can be viewed as a remarkable effect and instructive for the management of the PDT protocol. Regarding the relationship between the quantity of reactive oxygen species (ROS) and its biological consequences, we have proposed two mathematical models in PDT. Finally, we've gathered recent in vitro and in vivo studies about CCA post-PDT at various stages and made suggestions about how it can standardize, potentiate, and customize the PDT methodology.